Self-recognition and Well-being: Speaking Aboriginal English in Healthy Classrooms - Harrison, Neil (The Australian Journal of Indigenous Education, 2004)
Abstract This paper applies the findings of doctoral research undertaken in the Northern Territory. It draws on extended interviews with nine Indigenous students studying at university to produce four findings for classroom learning and teaching, one of which highlights the need to recognise Aboriginal English as a focal point of the curriculum for both Aboriginal and non-Aboriginal students. I take the position that this recognition in schools depends to a significant degree on universities training their preservice teachers to recognise Aboriginal English as necessary to Aboriginal student learning and therefore as a legitimate dialect of the classroom, and this in turn requires universities to recognise the importance of Aboriginal English in their own curricula. Towards the end of the paper, I draw on some literature to suggest ways in which Aboriginal English could be incorporated into the classroom.